KEARIFAN LOKAL MASYARAKAT NELAYAN PASER MAYANG DALAM PENGELOLAAN SUMBERDAYA PERIKANAN DI KECAMATAN KUARO KABUPATEN PASER - Eko Sugiharto; Qoriah Saleha; Agustina Maulida (CaLLs: Journal of Culture, Arts, Literature, and Linguistics)
The sampling technique uses the purposive sampling method, so the number of samples is 10. The results of the study show that: (1) The belief of the fishing community is a joint prayer performed by fishermen as a form of gratitude to God Almighty, with taboos, namely sweeping before going to sea is something that is prohibited because it is believed to throw away sustenance (catch), and prohibitions speak rudely, are dirty, slander other people, and may not fight among themselves, (2) Good ethics towards nature and its surroundings will also bring good catches, and the rules that are mutually agreed upon by local residents prohibit the use of fishing gear that can damage aquatic ecosystems, such as trawling, poison, and the use of bombs, and the separation of graves based on the tribes that occupy Pasir Mayang Village. (3) Techniques by looking at effective locations for catching fish, specifically in waters with currents, as evidenced by the numerous seagulls flying above these waters, and by utilizing technology efforts to use gelam bark, (4) Practices passed down from generation to generation include fishing activities that do not overfish, and the tradition that is carried out is the use of catches that are processed as shrimp paste, papaya, and salted fish, as well as carrying out mutual cooperation activities.